Contribution of central and peripheral adaptations to changes in maximal oxygen uptake following 4 weeks of sprint interval training - Raleigh, J. P.; Giles, M. D.; Islam, H.; Nelms, M.; Bentley, R. F.; Jones, J. H.; Neder, J. A.; Boonstra, K.; Quadrilatero, J.; Simpson, C. A.; Tschakovsky, M. E.; Gurd, B. J. (Applied Physiology, Nutrition, and Metabolism, 2018)
The current study examined the contribution of central and peripheral adaptations to changes in maximal oxygen uptake (VO2max) following sprint interval training (SIT). Twenty-three males completed 4 weekly SIT sessions (8 × 20-s cycling bouts at ~170% of work rate at V?O2max, 10-s recovery) for 4 weeks. Following completion of training, the relationship between changes in VO2max and changes in central (cardiac output) and peripheral (arterial-mixed venous oxygen difference (a-vO2diff), muscle capillary density, oxidative capacity, fibre-type distribution) adaptations was determined in all participants using correlation analysis. Participants were then divided into tertiles on the basis of the magnitude of their individual VO2max responses, and differences in central and peripheral adaptations were examined in the top (HI; ~10 mL/kg·min increase in VO2max, p < 0.05) and bottom (LO; no change in VO2max, p > 0.05) tertiles (n = 8 each). Training had no impact on maximal cardiac output, and no differences were observed between the LO group and the HI group (p > 0.05). The a-vO2diff increased in the HI group only (p < 0.05) and correlated significantly (r = 0.71, p < 0.01) with changes in VO2max across all participants. Muscle capillary density (p < 0.02) and ß-hydroxyacyl-CoA dehydrogenase maximal activity (p < 0.05) increased in both groups, with no between-group differences (p > 0.05). Citrate synthase maximal activity (p < 0.01) and type IIA fibre composition (p < 0.05) increased in the LO group only. Collectively, although the heterogeneity in the observed VO2max response following 4 weeks of SIT appears to be attributable to individual differences in systemic vascular and/or muscular adaptations, the markers examined in the current study were unable to explain the divergent V?O2max responses in the LO and HI groups.